From constitutional rule to loosely coupled spheres of liquid authority: a reflexive approach - Michael Zürn (International Theory, 2017)
This article develops a reason-based social foundation of new forms of authority, which often are liquid and sectorally limited. The recognition of authority hinges, in this view, on reflexive actors who are aware of their own limits of rationality regarding the lack of either information or a perspective that allows for the pursuit of common goods. In such a reflexive concept of authority, authority takers tend to monitor the authorities closely, and the internalization of the subordinate role is not a necessary part of it. Reflexive authority is embedded in the acceptance of a knowledge order that reproduces the authority relationship. In spite of a tendency toward institutionalization, reflexive authority often comes in a liquid state of aggregation, and almost always with a restricted functional scope. Moreover, this new set-up of authority creates social dynamics that add to liquidity. First, the encompassing constitutionalized rule with majoritarian decision making as major source of legitimacy is increasingly undermined by loosely coupled spheres of specialized authorities, which are most often justified on the basis of expertise. We can observe both the rise of international authorities in the absence of coordination between them, and the rise of similar authorities within the nation state that escape control of the democratic core institutions. As a result, authority gets fragmented and different authorities need to adjust to each other. The second implication of the argument is that democratic legitimation narratives become rare, leading to an ongoing legitimatory contestation of authorities. Both these processes make authority even more liquid.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich / This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; reflexive authority; legitimacy; spheres of authority; fragmentation; contestation; democratic paradox